Competitive quality strategies - Maillard, Pierre (London : ISTE ; Hoboken, NJ : John Wiley & Sons, 2013)
This book succinctly presents new methodological principles that will help you raise the quality of your valuable production to enhance your competitiveness. The concepts and models of principles of actions presented result from over 20 years of the author observing the ways in which companies of all sizes and in all sectors use specific mechanisms of quality production to give rise to long-lasting competitive factors. You'll find practical guides that will help you better understand and strengthen your approaches to create new competitive edges, based on your employees' culture of quality.
General principles of competitive quality / Pierre Maillard -- The definition of a competitive quality tactic / Pierre Maillard -- Deployment of a competitive quality tactic / Pierre Maillard -- The conditions for success of a competitive quality tactic / Pierre Maillard -- Selling a competitive quality tactic / Pierre Maillard -- Management of a competitive quality tactic / Pierre Maillard -- General conclusion -- Bibliography -- Index.
Online resource; title from pdf information screen (Ebsco, viewed February 7, 2013).
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Business planning; BUSINESS & ECONOMICS -- Strategic Planning; Business planning